Occupational Stressors Among Healthcare Workers in Hospital Seberang Jaya During Covid-19 Pandemic. A Qualitative Study. - Mohamad Imran, Daud (2021)
This qualitative study was conducted to explore the occupational stressors among healthcare workers in Hospital Seberang Jaya, Pulau Pinang during COVID-19 pandemic. By identifying the occurrence of the occupational stress and exploring the factors, mitigation plan and improvements can be developed to curb this issue. Data for this study was collected through semi-structured interview. Participants shared their feelings and experiences over open ended questions in the interview involving 8 selected healthcare workers across all departments in the hospital. All research findings captured and sorted in the research protocol. Moreover, Job Demand-Resources (JD-R) theory used in the research to comprehend the effect of the pandemic to their current job demands and resources. The research findings showed that most of the healthcare workers were having occupational stress and the main stressors are workloads, changing of Standard Operating Procedures (SOP) and prolongation of wearing Personnel Protective Equipment (PPE). This pandemic also made a major impact to their job demands and resources. Job demands were categorized into workplace safety and public perception while job resources are personal support and colleague’s support. Current interventions to manage occupational stress was also discussed in this study. Based on the finding and analyses, some suggestions and recommendations were made to handle occupational stress among healthcare workers.